hi my name is antonette Jane S pascua please help me my question thank you for your answer
Hello! And thank you for your question!
First we are going to expand the equation:
<span>−2<span>m^<span><span>2</span><span></span></span></span>−2mn+8m−10m+10n+nm+4<span>n<span><span>^2</span><span></span></span></span>−5n
Then we are going to combine like terms:
</span><span><span>−2<span>m<span><span>^2</span><span></span></span></span>+(−2mn+mn)+(8m−10m)+(10n−5n)+4<span>n<span><span>^2</span><span></span></span></span></span>
</span>
Then finally, simplify:
−2<span>m<span><span>^2</span><span></span></span></span>−mn−2m+5n+4<span>n<span>^<span>2
Final Answer:
</span></span></span>
−2m^2−mn−2m+5n+4n^2
So, to do this, you would multiply inside the radicals. The answer would be the fourth root of x^4, or x.
Answer:
Y=5
Step-by-step explanation:
x = -12( given)
-6 X( -12) -3y = 57
72-3y = 57
-3y=57-72
-3y= -15
Y=-15/-3
Y=5